Impact of transaction costs on intra Southern African migrants remittances - Mukadi, Basala (Research of GSB, 2018)
The average charges of officially transferring remittances from South Africa to other Southern African countries have been regarded as expensive compared to other main corridor of south-south remittance, and this has long been recognized as a major drain on the income of migrants and their households. Using data gathered across the SADC countries remittances corridors, this research explored the factors that account for the high costs of officially transferring remittances from South Africa to the SADC region. The average costs were regressed across all types of regulated financial institutions and money transfer operators with the following financial and macroeconomic variables: Real GDP per Capita, Dual exchange rates dummy, exchange rates, dollarization dummy, stock of migrants, volume of remittances, Exchange Control Restrictiveness Index, and the bank concentration. The study found that the main factors explaining the high costs of officially transferring remittances from South Africa to the SADC region were the bank concentration, exchange rate volatility, and the exchange control restrictiveness index. These findings suggest that the costs of officially transferring remittances from South Africa to the SADC region could be lowered by policies to increase competition among South African financial institutions and money transfer service providers, to reduce the country's exchange rate volatility, and to reduce the regulatory barriers that restrict financial services to migrants with non-South African identity documents.